Genetic and epigenetic analysis of schizophrenia in blood—a no-brainer?. Issue 1 (December 2016) - Jaffe, Andrew; Kleinman, Joel
Editorial summary Several recent studies have investigated either genetic or epigenetic variation in schizophrenia. A recent study presents comprehensive analyses of blood samples to better characterize the combined role of genetic and epigenetic variation in schizophrenia. While the paper identifies significant associations with schizophrenia risk and diagnosis, the potential relevance to the brain in schizophrenia is questionable.